2014
DOI: 10.1039/c4py00706a
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous and crystalline blends from polytyrosine and pyridine-functionalized anthracene: hydrogen-bond interactions, conformations, intramolecular charge transfer and aggregation-induced emission

Abstract: A new pyridine-terminated fluorophore of (E)-4-(2-(anthracen-9-yl)vinyl)pyridine (AnPy) with intramolecular charge transfer and aggregation-induced emission properties was synthesized and was blended with polytyrosine (PTyr) through hydrogen-bond interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…28 Recently, they also reported that (E)-4-(2-(anthracen-9-yl)vinylpyridine (AnPy) blended with different amounts of polytyrosine through hydrogen bond interactions exhibits intramolecular charge transfer (ICT) and AIE properties at a low AnPy content. 29 Building on the studies described above, in this work, we successfully synthesized 2,6-bis(4-aminophenyl)-4-phenylpyridine (Pyridine-NH 2 ) as the initiator for the living ring-opening polymerization of L-tyrosine-N-carboxyanhydride (NCA) to obtain Pyridine-PTyr (Scheme 1). We used photoluminescence spectroscopy to investigate the fluorescence characteristics of Pyridine-NH 2 and Pyridine-PTyr.…”
Section: Introductionmentioning
confidence: 99%
“…28 Recently, they also reported that (E)-4-(2-(anthracen-9-yl)vinylpyridine (AnPy) blended with different amounts of polytyrosine through hydrogen bond interactions exhibits intramolecular charge transfer (ICT) and AIE properties at a low AnPy content. 29 Building on the studies described above, in this work, we successfully synthesized 2,6-bis(4-aminophenyl)-4-phenylpyridine (Pyridine-NH 2 ) as the initiator for the living ring-opening polymerization of L-tyrosine-N-carboxyanhydride (NCA) to obtain Pyridine-PTyr (Scheme 1). We used photoluminescence spectroscopy to investigate the fluorescence characteristics of Pyridine-NH 2 and Pyridine-PTyr.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of dye 1 was achieved by adapting the ligand-free Heck reaction strategy reported by Yao et al [ 25 ], where the catalyst system consisted of Pd(OAc) 2 and K 3 PO 4 in dimethylacetamide (DMA) without any triaryl phosphine ligand. On the other hand, dye 2 was synthesized following the traditional Heck reaction strategy in the presence of the ligand PPh 3 [ 22 ]. The positively charged dye 3 was simply prepared from dye 2 by refluxing in CH 3 I, followed by ion exchange in the presence of KPF 6 as described in the Experimental section.…”
Section: Resultsmentioning
confidence: 99%
“…(E)-4-(2-(Anthracen-9-yl)vinyl)pyridine ( 2 ). The synthetic route towards ( 2 ) was adopted from the strategies previously described by Shih et al [ 22 ]. To an oven-dried 50 mL Schlenk tube were added 9-bromoanthracene (1.0 g, 3.9 mmol), K 2 CO 3 (1.6 g, 11.6 mmol), PPh 3 (153 mg, 0.6 mmol) and Pd(OAc) 2 (44 mg, 0.2 mmol).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the TP unit at the center of PBLG functioned as steric blocks, due to the α-helical conformation of PBLG peptide chain, and minimized the AIE behavior. Recently, Hong et al prepared blends of 2-(anthracen-9-yl)vinylpyridine (AnPy) and PTyr, stabilized through intermolecular hydrogen bonding, that displayed intramolecular charge transfer and AIE behavior [ 43 ]. In this present study, we employed 4,4′-diamino-4″-methoxytriphenylamine (TPA-NH 2 ) as an initiator for the preparation of PTyr-TPA through ring-opening living polymerization of an l -tyrosine- N -carboxyanhydride monomer.…”
Section: Introductionmentioning
confidence: 99%